Logistics performance review: European Union and ASEAN community - Salinee Santiteerakul (2018)
© 2018, ASERS Publishing House. All rights reserved. This paper explores the logistics performance within and between ASEAN Community (AC) and the European Union (EU). The study makes comparison and inspection based on World Bank’s Logistics Performance Indicators (LPI) of each economy and each collaboration. The finding shows big gap of logistics performance between economy in the collaboration. Where the EU is more advanced, and the gap is smaller, the AC is struggled with the improvement. The unbalanced level of performance within and between economies can be a big obstacle for future development as the global supply chain is unavoidable. The paper then discusses and suggests on the issues.